HUBUNGAN KECANDUAN MEDIA SOSIAL TERHADAP KESEHATAN MENTAL REMAJA PADA MASA PANDEMI COVID-19 - Amirah, Nurul; Jumaini, Jumaini; Indriati, Ganis (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p10, 2023)
The covid-19 pandemic has caused everyone to be isolated including teenagers, all activities are carried out online, this has led to an increase in the use of the internet to access social media as a means of communication. Adolescence is the transitional age from childhood to adulthood which is feared to have not been able to control the use of social media positively so that it has an impact on adolescents in the form of addiction.  The cross-sectional design was carried out on 89 respondents of adolescents at SMPN 5 Pekanbaru using aproportional random sampling technique. The Social Media Addiction Scale (SMAS) is used to measure the level of social media addiction, while the Strengths and Difficulties Questionnaire (SDQ) is used to measure mental health. Data analysis using the Chi-Square test and the Fisher test. Statistical results obtained results of no social media addiction to mental health with prosocial behavioral symptoms (p value 0,281), behavioral problems (p value 0,346), relationships with peers (p value 0,072) which means p value > ? (0,05), but in social media addiction and mental health emotional symptoms showed p value 0,001 and symptoms of hyperactivity (p value 0,036) which means p value < ? (0,05), there was a relationship between social media addiction to mental health with emotional symptoms. High use of social media can cause adolescents to experience mental health in the from of prosocial, emotional behavior, behavioral problems, hyperactivity, and problems eith peers.